2016
DOI: 10.1002/ijgo.12004
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing HPV vaccine delivery by healthcare professionals at public health posts in São Paulo, Brazil

Abstract: Knowledge and attitude played secondary roles in influencing HPV vaccine verification. Community health agents were crucial for vaccine promotion; continued education and support of this group is essential for the sustained success of HPV immunization efforts in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…There are few records in Latin American literature on adherence to the HPV vaccine after its implementation. What has been published highlights the lack of knowledge about HPV infection among Latin Americans, which is related to low education status and economic income [8][9][10]. Doubts about the vaccine's safety and efficacy, and cultural myths, such as HPV vaccination stimulating the onset of sexual life, are additional barriers for vaccine acceptance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are few records in Latin American literature on adherence to the HPV vaccine after its implementation. What has been published highlights the lack of knowledge about HPV infection among Latin Americans, which is related to low education status and economic income [8][9][10]. Doubts about the vaccine's safety and efficacy, and cultural myths, such as HPV vaccination stimulating the onset of sexual life, are additional barriers for vaccine acceptance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been associated with nonvaccination, including national priorities and fundings, access to healthcare, socioeconomic factors, as well as the attitudes of and knowledge on the part of health care professionals and relatives or caregivers [9][10][11][12][13]. In addition a number of factors influence acceptance of the HPV vaccine by relatives and caregivers: cultural and religious perceptions about sexual activity [14]; recognition that the vaccine is safe and effective [15]; fear of regretting the decision not to vaccinate; adherence to other routinely recommended vaccinations; social norms; and a positive influence from the media [16].…”
Section: Introductionmentioning
confidence: 99%
“…37 show that parents did not intend to vaccinate their daughters because of safety concerns and Figueroa-Downing et al 10 also found knowledge gaps related to vaccine safety in their study.…”
Section: Cheruvu Et Almentioning
confidence: 86%
“…In Brazil, Figueroa-Downing et al 10 and Osis et al 11 used a collection tool developed to describe the knowledge and attitudes of health professionals 10 and the lay population 11 . Collection instruments elaborated for situational analysis, although not generalizable, are exploratory in the sense of providing knowledge about a certain theme.…”
mentioning
confidence: 99%